Exploring Tax Accountants’ Experiences on Financial Reporting Quality in the Context of AI Intervention in Tax Audits - Pratama, Nesza; Tjaraka, Heru; Rahmiati, Alfa (Universitas Muhammadiyah Pontianak, 2025)
This study explores tax accountants’ perceptions of Artificial Intelligence (AI) intervention in tax audits and its impact on financial reporting quality. Using a Husserlian phenomenological approach and in-depth interviews with three accountants from various industries, the study finds that AI is seen as insufficient to grasp business context and professional values. The findings reveal risks of mechanistic reporting, triggering pseudo-compliance and manipulation to align with automated audit systems. The implication highlights the importance of AI audit systems that consider professional meaning and the complexity of fiscal reporting to ensure financial statements reflect business reality and maintain accountability and reporting integrity.